Sex differences in Guillain Barré syndrome, chronic inflammatory demyelinating polyradiculoneuropathy and experimental autoimmune neuritis - McCombe, Pamela A.; Hardy, Todd A.; Nona, Robert J.; Greer, Judith M. (Frontiers in Immunology, 2022)
Guillain Barré syndrome (GBS) and its variants, and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP and its variants, are regarded as immune mediated neuropathies. Unlike in many autoimmune disorders, GBS and CIDP are more common in males than females. Sex is not a clear predictor of outcome. The pathogenesis of GBS and CIDP involves immune response to non-protein antigens, antigen presentation through non-conventional T cells and, in CIDP, IgG4 antibody responses to antigens. There are some reported sex differences in these elements of the immune system and we speculate that these sex differences could contribute to the male predominance of these diseases.